Comprehensive Risk Assessment of Applying Biogas Slurry in Peanut Cultivation - Liu, Qingyu; Zhao, Zixuan; Xue, Zhiping; Li, Ding; Wen, Zhining; Ran, Yi; Mei, Zili; He, Li (Frontiers in Nutrition, 2021)
Biogas slurry, a byproduct of biogas plants, is considered a high-quality bio-organic fertilizer. Despite providing nutrients to crops, biogas slurry may contain a high concentration of heavy metals, leading to food safety problems and endangering human health if such metals are absorbed by plants. Therefore, biogas slurry should undergo systematic risk assessment prior to direct use on farmland to ensure its safety for soils and crops. In this study, the risk of applying biogas slurry in peanut cultivation was comprehensively evaluated. Based on nitrogen contents, different concentrations of biogas slurry were applied in peanut cultivation. The results achieved herein showed that the application of biogas slurry as a nutrient supplier in peanut cultivation would significantly affect the physical and chemical properties of soil and characteristics of the plant and the quality of peanuts. Although the heavy metal content of biogas slurry was within the permitted range, it had potential risks to human health and the environment. Principal component analysis (PCA) showed that biogas slurry was the primary source of heavy metals in soil. After the application of biogas slurry, the contents of As and Hg in the soil increased significantly, which were 11.12 and 26.67 times higher than those in the control soil. The contents of Cu, Zn, Pb, Cd, and As in peanut kernel samples under different levels of biogas slurry application were all lower than the maximum permissible limit set by the Standardization Administration of China. In contrast, the content of Hg in peanut kernels was higher than the maximum permissible limit value of 0.02 mg/kg. Peanut had a higher enrichment capacity of Cd and Zn and a higher migration capacity of Pb. The health risk assessment showed that the long-term consumption of peanuts grown with a high dosage of biogas slurry would be harmful to the health of children aged 2–6 years with a large consumption level.